Hsa_circRNA_103636: potential novel diagnostic and therapeutic biomarker in Major depressive disorder. (September 2016) - Cui, Xuelian; Niu, Wei; Kong, Lingming; He, Mingjun; Jiang, Kunhong; Chen, Shengdong; Zhong, Aifang; Li, Wanshuai; Lu, Jim; Zhang, Liyi
Aim: This study aimed to determine whether circular RNA (circRNA) molecules in peripheral blood mononuclear cells (PBMCs) could be used as novel non-invasive biomarkers for major depressive disorder (MDD).Materials & method s: Differentially expressed circRNAs were screened using an Arraystar Human CircRNA Array (which includes 13, 617 human circRNAs) and qRT-PCR. Thirty MDD patients were randomly selected to retest the circRNA levels after 4-week and 8-week antidepressant regimens.Results: Four differentially expressed circRNAs were identified between MDD patients and controls, and only down-regulated hsa_circRNA_103636 was significantly altered after the 8-week treatment in MDD patients.Conclusion: These results suggest that altered expression of hsa_circRNA_103636 in PBMCs is a potential novel biomarker for the diagnosis and treatment of MDD.